1993
DOI: 10.1093/infdis/168.4.888
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Meningitis in Infants <2 Years of Age: Diagnosis and Etiology

Abstract: Standard virologic methods were used to characterize the relative contribution of each of the enterovirus classes to the etiology of aseptic meningitis during a prospective study of this disease among children < 24 months old. Viruses were isolated in cell culture from 164 (60%) of 274 cases identified over 5 years and in newborn mice from only 2 of 104 remaining cell culture-negative cases. Serologic tests identified the viral pathogen in 3 additional cases. The group B coxsackieviruses and the echoviruses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(80 citation statements)
references
References 16 publications
4
72
0
4
Order By: Relevance
“…The findings of the present study have contributed to a better understanding of the epidemiology of these viruses in this region. We showed here that enterovirus is the main etiologic agent of viral meningitis in Curitiba and probably in the south Brazil, which is in accordance with different reports for other geographic regions 11,12 . The circulation of the enterovirus occurred mainly in the summer and autumn similarly to that described for the northern hemisphere.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study have contributed to a better understanding of the epidemiology of these viruses in this region. We showed here that enterovirus is the main etiologic agent of viral meningitis in Curitiba and probably in the south Brazil, which is in accordance with different reports for other geographic regions 11,12 . The circulation of the enterovirus occurred mainly in the summer and autumn similarly to that described for the northern hemisphere.…”
Section: Discussionsupporting
confidence: 92%
“…In other countries [Berlin et al, 1993;Trallero et al, 2000], a variety of enterovirus serotypes were also identified as the causative agent of viral meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…CB4 strain JVB was obtained from the ATCC. CB5 88-0578, a lowpassage clinical isolate provided by John Modlin (Dartmouth Medical School), was previously described (6,12). Viruses were expanded by growth in HeLa cells and concentrated by ultracentrifugation through a sucrose cushion, and titers were determined by plaque assay using HeLa cells.…”
Section: Methodsmentioning
confidence: 99%